Closer Look at the New Processor: 80386 - Shaikh, Hamira; Shaikh, Mosina; Shaikh, Shahid; Qureshi, Aatif; Khan, Farman; Patel, Viren; Shaikh, Shakila; Pappu, Shiburaj (International Journal of Computer Sciences and Engineering, 2019)
Intel has launched a 32bit microprocessor which was designed for high performance and to drive the most advanced computer-based applications. The 80386 offers the system designer many new and powerful capabilities, including unprecedented performance of 3 to 4 million instructions per second. The addressing modes of 80386 support efficient access to the elements of the standard data structures.